Non-Litigatory Dispute Resolution Regarding Medical Device Procurement Contracts by Medical Device Distributors Related to its Implementation that Does Not Conform to the Agreement - Subrata, Adi Irama; Marniati, Felicitas Sri; Mulyadi, Mulyadi (Journal of Legal and Cultural Analytics, 2025)
This legal research examines the legal consequences and non-litigation dispute resolution for non-conforming medical device procurement contracts between distributors and buyers in Indonesia. Based on contract law, specifically Articles 1320 and 1338 of the Indonesian Civil Code, it applies Dean G. Pruitt's Dispute Resolution Theory and R. Soeroso's Legal Consequence Theory. Using a normative juridical methodology, the study combines statutory, conceptual, analytical, and case approaches. Data from primary, secondary, and tertiary sources were analyzed grammatically, systematically, and analogically. Findings indicate non-conforming contracts create new obligations, alter relationships due to breaches, and trigger legal sanctions. Disputes can be resolved through problem-solving, yielding mutually beneficial solutions, such as replacing goods to meet agreed quality and quantity.